A cost-effectiveness analysis of two psychological treatments for controlled drinking in individuals with alcohol use disorder - Sergio Flores; Egill Jónsson-Bachmann; Stina Ingesson-Hammarberg; Anders Hammarberg; Camilla Nystrand; Filipa Sampaio (Cost Effectiveness and Resource Allocation)
Abstract Background and aims In Sweden, up to 7% of people exhibit harmful alcohol use or dependency, but only a small fraction (10–20%) pursue treatment. While Behavioral Self-Control Training (BSCT) and Motivational Enhancement Therapy (MET) are effective for alcohol use disorders (AUD), their cost-effectiveness has not been studied. This research evaluates the cost-effectiveness of BSCT and MET in treating AUD, focusing on achieving controlled drinking from both a healthcare and limited societal perspective. Design, setting, and participants A Markov model was created to compare the cost-effectiveness of BSCT and MET for treatment-seeking individuals with AUD. This model simulated a sample of patients with AUD over five years, calculating the costs and outcomes for both treatments. It used a cost-utility analysis to determine the cost per quality-adjusted life year (QALY). The model accounted for varying levels of alcohol intake and related health complications. Efficacy data came from a randomized trial, with complication risks, costs, utilities, and mortality rates drawn from existing literature. Intervention and comparator BSCT, consisting of five sessions, was compared to MET, constituted by four sessions. Measurements The primary outcome was cost per QALY. Probabilistic and univariate sensitivity analyses were performed to estimate how parameter uncertainty affected model outputs. Findings BSCT proved less costly than MET, yielding savings in healthcare costs by $50.52 and societal costs by $118.12 on average per person. Additionally, BSCT demonstrated an advantage in QALYs, with a gain of 0.060 QALYs per patient over MET. Sensitivity analyses confirmed the robustness of these results, indicating that BSCT is the cost-effective treatment option. Conclusions In comparison to MET, BSCT is less costly and more beneficial for health, indicating its potential as a valuable treatment option for individuals with AUD targeting controlled drinking. The model can be applied to assess the cost-effectiveness of various other AUD treatment interventions.